Media Point of View on 10 Years of Syiria Conflict: A Functional Grammar - Isti'anah Isti'anah; Abdul Muta'ali (Arabic Literature Department, 2022)
As a source of information, the media can have an influence on its readers, both positive and negative influences. The influence gained by the reader actually comes from the writer who consciously or not forms a certain point of view. As is the case with the news of Syrian conflict that has occurred for a long time. Through transitivity analysis, it is hoped that it will be able to provide an overview of how the media views the event. The purpose of this study was to determine the results of transitivity analysis which was able to describe the media’s point of view on a news story. The data sources used in this research are aljazeera.net and ahram.org. The theory used to analyze the data is the three elements of transitivity from Halliday and Matthiessen, namely process, participant, and circumstantial. The results of this study indicate that there is a difference int the dominance of the use of the process between the two media. Al-Jazeera is more dominant in using material process and Al-Ahram is dominant in mental process. Both media portray participants from the same angle, namely to make Iran dan Rusia as active participants or actors.